The initial experience and outcomes of patent ductus arteriosus closure at Nelson Mandela Academic Hospital, Mthatha, Eastern Cape: Patent ductus arterioles closure using Ampletzer - Makrexeni, Z.M.; Bobotyana, L. (SA Heart Journal, 2025)
Background: Transcatheter closure of the patent ductus arteriosus (PDA) is a common intervention worldwide. An initial experience and outcomes in percutaneous closure of patent ductus arteriosus in a new catheterisation laboratory at Nelson Mandela Academic Hospital (NMAH) in Mthatha was reviewed. Methods: Data regarding ductal closure using the Amplatzer Duct Occluder type 1 (ADO1) and Amplatzer Vascular Plug II (AVP II) were reviewed and prospectively collected. Demographics, haemodynamics, angiographic patent ductus arteriosus type, complications and outcomes were documented. Results: A total of 26 patients underwent percutaneous patent ductus arteriosus closure from September 2019 - August 2021(1year 11 months). There were 17 females and 9 males. The median age of the patients was 23 months (range 3 - 60 months) and the median weight was 8.3kg (range 3.6 - 14kg). The mean pulmonary vascular resistance was 4 Wood unit (WU). Seven patients had Krichenko Type C Duct (27%) and 15 (58%) patients had Type A Duct. The ductal size (narrowest diameter at the pulmonic end) mean was 6mm for the Type C Ducts and 3.5mm for the Type A Ducts. Fluoroscopy time was mean was 18 minutes and the radiation dose was about 450 microGreys. Out of the 26 patients that were done catheterisation, 4 patients were not done patent ductus arteriosus closure. Of the 4 patients, 2 patients had tiny PDAs that could not be closed percutaneously, and the other 2 patients had associated coarctation of the aorta. Six of the 7 patients with Type C Duct were closed successfully with Amplatzer Vascular Plug, and 1 patient had device embolisation. Fifteen patients with Type A Duct were closed successfully with Amplatzer Ductal Occluder 1 with no complications. Complete ductal occlusion was achieved in 21 patients on day 1 and only 1 patient had residual ductal flow following the ductal closure. Conclusion: Percutaneous ductal closure with Amplatzer Duct Occluder at Nelson Mandela Academic Hospital is comparable to other centres in South Africa in terms of safety and outcomes.